Sociocognitive rhythmic physical activity to improve basic movement skills in primary learners - Riky Dwihandaka; Joko Nurkamto; M Furqon Hidayatullah; Fauzi; ihsan, fadli (Jurnal Cakrawala Pendidikan, 2025)
Rhythmic physical activity has the potential to enhance fundamental movement skills in children aged 8–9 years; however, research on this topic remains limited. The objective of this study was to examine the effectiveness of socio-cognitive-based rhythmic physical activity in improving the fundamental movement skills of elementary school students aged 8–9 years. A total of 40 students (20 boys and 20 girls) were randomly assigned to either an experimental group or a control group. Both groups participated in a four-week intervention program conducted three times per week. Fundamental movement skills were assessed using the Test of Gross Motor Development-3 Short Form (TGMD-3 Short Form) one day before and after the intervention. After the four-week intervention, the experimental group demonstrated a significant improvement in fundamental movement skills. All seven items of the TGMD-3 Short Form showed statistically significant enhancements: hop with one leg (p < 0.05), Gallop (p < 0.05), long jump from place (p < 0.05), overhand throw (p < 0.05), two-handed catch (p < 0.05), stationary dribble (p < 0.05), and two-handed strike (p < 0.05). This study provides empirical evidence that an eight-week socio-cognitive-based rhythmic physical activity program significantly improves the fundamental movement skills of children aged 8–9 years. The improvement in movement skills was greater in children who participated in the socio-cognitive rhythmic physical activity program compared to those who engaged in general physical activities. This rhythmic activity model can serve as an effective alternative learning material for rhythmic activity instruction in elementary schools.